Ihsan Reflection Model (IRM): a holistic framework for ethical insight in Islamic accounting and finance - Mohamad, Siti Rohana; Azmi, Nur Farahiah; Jamil, Amira; Abdullah, Tahirah; Abdullah, Siti Salwani (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Ethics has great significance in education that serves as the cornerstone of Islamic society, ensuring a comprehensive framework for teaching in its effort to humanise education. As new technological changes and developments occur, many challenges also grow globally. The entire world is becoming mechanical and commercial with the expectation of honesty and commitment being more of a dream now. Due to this, a great demand for ethics to inculcate and develop morality and values among youths has increased in education. Ihsan Reflection Model (IRM), based on Gibbs' Reflective Cycle (1988), is a structured framework consisting of six stages that guide individuals through reflection, learning, and ethical development in Islamic financial decision-making. This model aims to cultivate well-rounded individuals with strong faith, knowledge, and noble character so that eventually, they will have a solid ethical foundation rooted in Islamic moral values. Integrating Islamic ethical principles with reflective writing in education, personal and professional life, can significantly enhance moral resilience, accountability, and ethical leadership. This integration ensures long-term integrity and success. As a result, this approach stimulates students' interest and encourages structured self-reflection, lifelong learning, critical thinking, and continuous development.